Pengaruh kepemimpinan instruktif dan keadilan organisasi terhadap perilaku menyimpang karyawan melalui kepercayaan organisasi sebagai variabel intervening - Heriyanto, Peyi (Journal of Economics, Business, Accounting and Management, 2023)
This study aims to determine the influence of Instructive Leadership and Organizational Justice to the Organizational Belief of Gadjah Mada University, to know the influence of Instructive Leadership and Organizational Justice to the Deviant Behavior of Gadjah Mada University Employees, to know the influence of Organizational Beliefs on Employee Deviant Behavior of Gadjah Mada University, Instructive Leadership and Organizational Justice to the Deviant Behavior of Employees of Gajah Mada University through Organizational Trust. This research method with quantitative approach, that is descriptive test and inferential analysis by using path analysis tool. The data collection technique using questionnaires, where the respondents of the research are employees of the education staff of Gadjah Mada University, this research which will be the research sample is the staff of the educational staff that number is spread in 18 Faculties and one vocational school. The results are expected to be in line with the objectives of the study and meet the expectations of researchers, enterprises and stakeholders